6 - Globalisation, Internationalisation and Higher Education in Mauritius: The Compromise of Quality - Ramtohul, Ramola (Africa Development, 2021)
This article discusses the implications, risks and benefits of globalisation and internationalisation of higher education in Mauritius. Mauritius is one of Africa’s success stories in terms of political stability, democracy, peace and development. Being a resource-poor country and because of the remoteness and small size of the island, diversity of the population and lack of indigenous culture, Mauritius has always been closely connected to the global economy and society. Given the absence of high-value natural resources, a key resource the csuntry has had to rely on is human capital and Mauritius has invested heavily in education through the welfare state which provides free education at all levels. In order to widen access to higher education, the Mauritian government has opened up the sector to foreign higher education institutions. A growing number of Western and Indian foreign accreditation bodies offer courses in the country in parallel with the local tertiary institutions. The article shows that while Mauritius has been open to internationalisation to enable the higher education sector to grow, this is taking place at a substantial financial cost, which is to the detriment of the quality of education and also to local higher education and examination bodies. The sector has become riddled with corruption as politicians bypass regulations and quality for financial gain. Moreover, the form and direction that internationalisation is taking is highly imbued with a Western bias which is more expensive, does not encourage the development of local knowledge and also portrays an image that western academic certificates carry a higher value. Mauritius is also not linking up sufficiently with African higher education institutions, apart from a few South African universities.